1976
DOI: 10.1016/0002-9610(76)90158-6
|View full text |Cite
|
Sign up to set email alerts
|

Postgastrectomy syndromes

Abstract: Postgastrectomy syndromes requiring further operation are fortunately uncommon, as the symptoms are disabling and the results of corrective surgery are, at times, disappointing. Our sixty-six patients underwent a total of seventy-six procedures with forty-one successful results and thirty-five failures. Among the secessful group, only fourteen results were graded as excellent. (Table V.) Our experience, like that of others, demonstrates the necessity of accurate evaluation of the patient and of accurate syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1978
1978
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…IN an appreciable number of patients the results of operations for the cure of peptic ulcer are marred by reflux of bile into the stomach, setting up a gastritis easily recognizable at endoscopy (Brooke-Cowden et al, 1976) with characteristic histological changes in the mucosa (Drapanas and Bethea, 1974). This causes severe burning or boring epigastric pain in the great majority of patients and is usually associated with vomiting of bile.…”
mentioning
confidence: 99%
“…IN an appreciable number of patients the results of operations for the cure of peptic ulcer are marred by reflux of bile into the stomach, setting up a gastritis easily recognizable at endoscopy (Brooke-Cowden et al, 1976) with characteristic histological changes in the mucosa (Drapanas and Bethea, 1974). This causes severe burning or boring epigastric pain in the great majority of patients and is usually associated with vomiting of bile.…”
mentioning
confidence: 99%
“…1,2 Loss of body weight is an important characteristic of postgastrectomy syndromes; 3,4 however, the exact reasons for weight loss after total gastrectomy are still unclear. Acceleration of small intestinal transit, supposedly resulting in a decreased contact time of chyme with the small intestinal mucosa, has been blamed, but others have found that small intestinal transit is slowed after total gastrectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Anemia usually is due to iron deficiency and is noted in over half of the patients following gastric surgery [49], The occurrence of a symptom complex suggestive of bile reflux in a patient with a history of gastric surgery in the past raises other possibilities, such as recurrent peptic ulcer disease, gastric outlet obstruction, and afferent loop obstruction. 'Dumping-plus' is a variant of this syndrome which refers to the coexistence of the early dumping syn drome and bilious vomiting in the same pa tient [50]. Hypochlorhydria [47] is a com mon finding.…”
Section: Diagnosismentioning
confidence: 99%